The Role of Positionality in Teaching for Critical Consciousness: Implications for Adult Education - Edward Taylor; Elizabeth J. Tisdell; Mary Stone Hanley (Adult Education Research Conference, 2000)
This paper examines how differences in positionality of the three co-authors (as a white man, a white woman, and an African-American woman) informs both the theorizing and the differences in practice of education for critical consciousness in adult higher education settings.